Mycoflora associated with infected fruits of Momordica cochinchinensis (Lour.) Spreng. (Bangladesh Journal of Plant Taxonomy, 2016)
Eleven species of anamorphic fungi associated with anthracnose and fruit rot symptoms of Momordica cochinchinensis (Lour.) Spreng. (Ban Kakrol) have been described. The associated fungi were Aspergillus niger Van Tieghem, Colletotrichum gloeosporioides (Penz.) Sacc., C. orbiculare (Berk. & Mont.) Arx., Corynespora cassiicola (Berk. & Curt.) Wei, Curvularia clavata Jain, Dendryphiella vinosa (Berk. & Curt.) Reisinger, Fusarium moniliforme J. Sheld., Lasidiodiplodia theobromae (Pat.) Griff. & Maubl., Pestalotiopsis guepinii (Desm.) Stey., Penicillium digitatum Sacc. and Xylohypha pinicola D. Hawksw. Xylohypha pinicola is a new record for Bangladesh.Bangladesh J. Plant Taxon. 23(2): 181-188, 2016 (December)